2022
DOI: 10.1155/2022/1766776
|View full text |Cite|
|
Sign up to set email alerts
|

Model Construction of Dance Teaching System for College Students under the Background of Information Technology

Abstract: The rapid growth of computer network technology has changed the way people communicate and learn. The way of acquiring knowledge is also much more advanced than before. Under the guidance of correct teaching methods and teaching thinking, dance teaching methods must try new methods, adjust teaching contents, and change narrow inertia thinking. Online distance education is a new type of education method that transcends the time and space limitations of traditional education methods, making it easier for more pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The result refuted the findings of Li et al (2018) wherein despite of initial difficulties, students benefit from technology integration in dance. Similarly, the findings of Zhou (2022) revealed that introducing information technology into dance education can optimize resources, enrich the performance context of dance education, broaden the opportunities for both teachers and students, and the application of IT for direct appreciation and design. It can be determined that even though the students have a higher level of acceptance and actual use of YouTube and Facebook, it negatively impacts their engagement in learning and dancing, and in the promotion of the Philippine traditional dances.…”
Section: Discussionmentioning
confidence: 99%
“…The result refuted the findings of Li et al (2018) wherein despite of initial difficulties, students benefit from technology integration in dance. Similarly, the findings of Zhou (2022) revealed that introducing information technology into dance education can optimize resources, enrich the performance context of dance education, broaden the opportunities for both teachers and students, and the application of IT for direct appreciation and design. It can be determined that even though the students have a higher level of acceptance and actual use of YouTube and Facebook, it negatively impacts their engagement in learning and dancing, and in the promotion of the Philippine traditional dances.…”
Section: Discussionmentioning
confidence: 99%
“…Effective use of formative assessment in this research is defined as an effective means of tracking student progress and identifying areas in need of improvement (Dean, 2007;Bennett, 2011;Antoniou and James, 2014;Andrade et al, 2015;Spector et al, 2016;Rasooli et al, 2018). Through real-time monitoring, teachers can provide targeted guidance and support to enhance overall learning outcomes (Schmid, 2012;Andersson, 2014;Li, 2020;Zhou, 2022). By implementing a formative assessment task focused on online Popping dance, instructors can quickly assess student proficiency and adjust their teaching methods accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the traditional form of education in the classrooms of an educational institution has remained almost unchanged. However, the distance form of education has been an integral part of the educational process for more than a decade, becoming a dominant one this year during the pandemic and the destabilization of the political situation in the world (Zhou, 2022).…”
Section: Introductionmentioning
confidence: 99%